2021
DOI: 10.4314/njpr.v16i2.15s
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Susceptibility Pattern of Bacteria Isolated from Ready-To-Eat Vegetables Sold in Mohammadu Gumi Market, Kaduna, Nigeria

Abstract: Background: Freshly consumed vegetables are considered to have more nutritional value than cooked ones. However, they are a potential source of foodborne illnesses due to possible microbial contamination, this poses safety threat.Objectives: This study was carried out to determine the bacteriological quality of ready-to-eat vegetables sold in Mohammadu Gumi market, Kaduna and to determine the antibiotics resistance pattern of the bacteria isolates.Methods: A total of 40 samples of cabbage were collected. Gram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Only 1 isolate harboured all three genes namely CTX-M, TEM and SHV. Data obtained from this study correlate with report from other researchers Obajuluwa et al [36] who showed that ESBLs genes may vary from source of infection to another and from one location to another. Other studies have also implicated other bacterial isolates such as Proteus mirabilis as reservoirs of these resistance genes.…”
Section: Resultssupporting
confidence: 90%
“…Only 1 isolate harboured all three genes namely CTX-M, TEM and SHV. Data obtained from this study correlate with report from other researchers Obajuluwa et al [36] who showed that ESBLs genes may vary from source of infection to another and from one location to another. Other studies have also implicated other bacterial isolates such as Proteus mirabilis as reservoirs of these resistance genes.…”
Section: Resultssupporting
confidence: 90%
“…The suspected bacterial isolates were ten (10) Coagulase Negative Streptococci (63%), four (4) Staphylococcus aureus (25%), one (1) Streptococcus pneumoniae (6%), and one (1) Streptococcus pyogenes (6%). In a related study by Obajuluwa et al 23 more gram negative organisms were isolated, out of a total of 46 bacteria isolates which disclosed the following bacterial isolate: Staphyloccocus aureus (41.3%), Escherichia coli (28.3%), Salmonella spp (19.6%), Pseudomonas aeruginosa (8.7%) and Serratia spp (2.2%). According to Kayode et al 24 gram positive bacteria isolates from selected vegetables were similar to this present study where all isolates were gram positive; and the bacterial isolates from cabbage include; Brevibacillus laterosporus, and Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 96%